2019
DOI: 10.1111/ijau.12169
|View full text |Cite
|
Sign up to set email alerts
|

Narrative disclosures, firm life cycle, and audit fees

Abstract: This study examines the relationship between narrative disclosure properties in terms of readability, optimism, and ambiguity of annual reports and audit fees, and how the relationship changes across firms' various life‐cycle stages. Using 54,883 observations for the years from 2000 to 2016, we find that these textual disclosure properties have positive audit pricing consequences. We suggest that narrative disclosure properties play an important role in estimating audit risk, and thus in audit fees. We further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 89 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, Hossain M investigated the impact of narrative disclosure features on audit fees and found that they had a positive impact on audit pricing and showed different effects at different stages of the company’s transformation. It emphasizes the dynamic nature of the firm and the importance of considering the stage of the firm’s life cycle when analyzing the relationship between narrative disclosure characteristics and audit costs [ 6 ]. In the pursuit of proficiency in skills and the relevance of information systems to business management in the digital age, Sihite M conducted an extensive review, uncovering a significant correlation between skills and successful business management [ 7 ].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, Hossain M investigated the impact of narrative disclosure features on audit fees and found that they had a positive impact on audit pricing and showed different effects at different stages of the company’s transformation. It emphasizes the dynamic nature of the firm and the importance of considering the stage of the firm’s life cycle when analyzing the relationship between narrative disclosure characteristics and audit costs [ 6 ]. In the pursuit of proficiency in skills and the relevance of information systems to business management in the digital age, Sihite M conducted an extensive review, uncovering a significant correlation between skills and successful business management [ 7 ].…”
Section: Related Workmentioning
confidence: 99%
“…) ‫بب‬ ‫بحلبييا:ب‬ ‫،لبثهعحبحثحاب‬ ‫ق‬ ‫ب‬ Flesch Reading Ease Index, flesh-kincaid grade; Fog Index, Bog Index‫;ب‬ SMOG Index, Lix Index, Cloze Procedure. (Li, 2008;Lo et al, 2017;Xu et al, 2020 (Callaghan et al, 2008;Yuniarti, 2011;El-Gammal, 2012;Barua et al, 2020;Chakrabarty et al, 2020 (Simunic, 1980;Kim and Fukukawa, 2013;Woo & Lim, 2015;Jiang and Son, 2015;Hossain et al, 2019;Salehi et al, 2020;Saghafi et al, (Hossain & Salama, 2018;Hossain et al, 2019;Salehi et al, 2020;Xu et al, 2020;Wang et al, 2021;Castro et al, (Hamers et al, 2016;Habib and Hasan, 2017;2019;Krishnan et al, 2021;Yoo et al, 2019;Akbar et al, 2019;Hussain et al, 2020;Can, 2020 (Hossain & Salama, 2018;Cho et al, 2019;Abernathy et al, 2019;Hossain et al, 2019;Castro et al, 2019;Blanco et al, 2020;Xu et al, 2020;Salehi et al, 2020;Karim and sarkar, 2020;Kazemiolum et al, 2020;Wang et al, (Cho et al, 2019;...…”
Section: ‫البحث‬ ‫ممخص‬mentioning
confidence: 99%
“…During the fee negotiation process, auditors spend a substantial amount of time and effort collecting and evaluating both qualitative and quantitative information about their clients (Brazel et al ., 2009; Greiner et al ., 2020). Because auditors analyse all client‐specific information when determining the pricing of audit services (Simunic, 1980; Brazel et al ., 2009; Abernathy et al ., 2019), textual disclosures assist auditors in evaluating engagement risks and structuring audit fees (Hossain et al ., 2019). Previous literature indicates that textual disclosures are informative and play a critical role in the evaluation of a firm’s business operations, risk profile, and financial condition (Campbell et al ., 2014; Loughran and McDonald, 2016).…”
Section: Literature and Hypothesismentioning
confidence: 99%
“…However, Hossain et al . (2019) suggest that an overly optimistic tone in a client’s textual disclosures increases the auditor’s professional scepticism and audit effort, resulting in higher audit fees. More recently, Greiner et al .…”
Section: Literature and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation